2021
DOI: 10.9734/jpri/2021/v33i631185
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus: Infection, Immunological Response, and Vaccine Development

Abstract: In the tropics and subtropics climates worldwide, the dengue virus (DENV) is the most common of arboviruses and a significant public health threat. The severe disease usually occurs during the primary infection, but more serious cases begin after the second instance of infection with a different serotype. Humans' innate immune system is composed of monocytes, macrophages, and dendritic cells, and they are capable of mounting rapid inflammatory responses. These cells are also called primary antigen-presenting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Studies have confirmed the role of Sphingosine kinase (SK1) in the TNF-α-mediated elicitation of inflammation via NFκB [ 53 , 54 ]. Netosis or NET (Neutrophil extracellular traps) formation by neutrophils is an interesting feature observed in patients suffering from Dengue Hemorrhagic Fever (DHF), with evidence of dire nuclei decondensation [ 55 , 56 ]. Other strategies employing microRNAs (miRNAs) to alleviate the severe inflammatory conditions in DENV patients are being explored.…”
Section: Inflammation During Dengue Virus Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have confirmed the role of Sphingosine kinase (SK1) in the TNF-α-mediated elicitation of inflammation via NFκB [ 53 , 54 ]. Netosis or NET (Neutrophil extracellular traps) formation by neutrophils is an interesting feature observed in patients suffering from Dengue Hemorrhagic Fever (DHF), with evidence of dire nuclei decondensation [ 55 , 56 ]. Other strategies employing microRNAs (miRNAs) to alleviate the severe inflammatory conditions in DENV patients are being explored.…”
Section: Inflammation During Dengue Virus Infectionmentioning
confidence: 99%
“…Neutrophils are also recruited to the primary site of infection by the tissue-resident macrophages through the secretion of IL-8, TNF-α, and IFN-β. Antiviral factors such as TNF-α and defensins are generated by neutrophils [ 55 ]. Moreover, the degree of complement activation by the DENV-NS1 protein is greater in DHF patients than in mild/intermediate Dengue Fever (DF) [ 73 ].…”
Section: Host Immune Cell Responses To Dengue Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue virus (DENV) is a single-stranded positive RNA virus that has a round virion with a size of 50 nm consisting of three structural proteins, namely capsid (C), pre-membrane/membrane (prM/M), and envelope (E), and seven nonstructural proteins (NS), namely NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5, which are directly involved in assembly and replication of DENV (Sindi, 2021). Protein E and NS5 can be used as targets for dengue infection.…”
Section: Introductionmentioning
confidence: 99%